Manajemen Pemeliharaan Ayam Boiler di Anjas Farm Kabupaten Maros - Nugraha, Angga; Ananta Syam, Gifar; Aldiansyah, Rahmat; Syuaib, Abdulrahman (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
The purpose of this activity is to understand the management of broiler chicken maintenance carried out by internship students of the Animal Husbandry Study Program, Universitas Muhammadiyah Sidenreng Rappang, at Anjas Farm. Broiler chicken maintenance is carried out through three main stages: cage cleaning, cage preparation, and maintenance phases including pre-starter, starter, and finisher. Each phase has specific treatments related to feed, temperature, cleanliness, and chicken development evaluation. The results of the activity show that students are able to understand and practice the stages of broiler chicken maintenance management systematically and applicatively in the field. Increase students' understanding of broiler chicken maintenance management, improve skills in practicing broiler chicken maintenance, and enhance professional attitudes in managing broiler chicken farms. Furthermore, this activity can provide practical experience for students to face challenges and situations that may occur in the field, thereby enhancing their readiness to enter the workforce in the field of broiler chicken farming. It is hoped that the internship activities at Anjas Farm will provide significant benefits for students and improve the quality of graduates ready to compete in the broiler chicken farming industry.